Opening The Black Box of Women LED-SMEs: How Does Agility Impact Entrepreneurial Performance? - Susanti Dwi Ilhami; Damayanti Damayanti (Business Management Analysis Journal (BMAJ), 2026)
Strengthening entrepreneurial performance is an essential to achieve greater equality and enhance their roles in economic development. This research aims to examine the mediating role of innovativeness and the moderating role of technology adoption in the relationship between agility and women’s entrepreneurial performance. There were 140 Muslim women entrepreneurs in Rembang Regency who are chosen by using purposive sampling based on predetermined principles. The data collection was obtained through structured questionnaires and also being analyzed by using the Structural Equation Modelling–Partial Least Squares (SEM-PLS) approach. The results indicate that agility significantly impacts women’s entrepreneurial performance and innovativeness. However, innovativeness does not significantly contribute to entrepreneurial performance. In addition, innovativeness was not found to be a mediator variable in the relationship between agility and performance, and technology adoption did not moderate this relationship. The study supply to a deeper consideration of women’s entrepreneurial behavior and provides practical insights for Muslim women entrepreneurs to strengthen agility and innovation capabilities in order to enhance their performance and advance gender equality.